Different Forms of ER Stress in Chondrocytes Result in Short Stature Disorders and Degenerative Cartilage Diseases: New Insights by Cartilage-Specific ERp57 Knockout Mice. (17th December 2018) - Rellmann, Yvonne; Dreier, Rita
Abstract : Cartilage is essential for skeletal development by endochondral ossification. The only cell type within the tissue, the chondrocyte, is responsible for the production of macromolecules for the extracellular matrix (ECM). Before proteins and proteoglycans are secreted, they undergo posttranslational modification and folding in the endoplasmic reticulum (ER). However, the ER folding capacity in the chondrocytes has to be balanced with physiological parameters like energy and oxygen levels. Specific cellular conditions, e.g., a high protein demand, or pathologic situations disrupt ER homeostasis and lead to the accumulation of poorly folded or misfolded proteins. This state is called ER stress and induces a cellular quality control system, the unfolded protein response (UPR), to restore homeostasis. Different mouse models with ER stress in chondrocytes display comparable skeletal phenotypes representing chondrodysplasias. Therefore, ER stress itself seems to be involved in the pathogenesis of these diseases. It is remarkable that chondrodysplasias with a comparable phenotype arise independent from the sources of ER stress, which are as follows: (1) mutations in ECM proteins leading to aggregation, (2) deficiencies in ER chaperones, (3) mutations in UPR signaling factors, or (4) deficiencies in the degradation of aggregated proteins. In any case, the resulting UPR substantially impairs ECM protein synthesis, chondrocyte proliferation, and/or differentiation or regulation of autophagy and apoptosis. Notably, chondrodysplasias arise no matter if single or multiple events are affected. We analyzed cartilage-specific ERp57 knockout mice and demonstrated that the deficiency of this single protein disulfide isomerase, which is responsible for formation of disulfide bridges in ECM glycoproteins, is sufficient to induce ER stress and to cause an ER stress-related bone phenotype. These mice therefore qualify as a novel model for the analysis of ER stress in chondrocytes. They give new insights in ER stress-related short stature disorders and enable the analysis of ER stress in other cartilage diseases, such as osteoarthritis.